RELEVANSI PASAL 82 AYAT 2 UNDANG-UNDANG NOMOR 40 TENTANG PERSEROAN TERBATAS MENGENAI TATA CARA PEMANGGILAN RUPS MELALUI IKLAN DALAM SURAT KABAR - Yuda, I Gede Indra Vitata; Perbawa, Kt. Sukawati Lanang P. (Jurnal Hukum Mahasiswa, 2024)
In a Limited Liability Company (LLC), the primary responsibility for running the company lies with the board of directors and commissioners, who act as extensions or executors of the rules of investors or shareholders. They are responsible for adhering to the provisions in the articles of association and the Company Law and managing the company according to the principles of Good Corporate Governance (GCG) such as justice, transparency, and accountability.One crucial aspect of implementing the provisions in the articles of association and the Company Law is holding the General Meeting of Shareholders (GMS). The Company Law explains the procedures for conducting GMS from the beginning to the formation of GMS decisions. In this study, the author analyzes juridical aspects and legal implications of the procedure for convening GMS through advertisements in newspapers, as regulated in Article 82 paragraph (2) of the Republic of Indonesia Law Number 40 of 2007 Concerning Limited Liability Companies, to determine its continued relevance. This study uses a normative research method focusing on examining the application of a legal norm using legal sources such as primary legal materials, secondary legal materials, and tertiary legal materials.